PERAMALAN TINGGI GELOMBANG PECAH DI GARIS PANTAI KECAMATAN PANCENG KABUPATEN GRESIK - Syah Putra Aira Loka Loka; Iwan Wahjudijanto; Minarni Nur Trilita (CI-TECH, 2021)
Shoreline is a line where the edge of the land and the sea met. Various amount of shore construction was built around the shoreline. The safety of surrounding community near the shoreline should be considered before the government planning on near shore and shoreline facility. Therefore, breaking waves height become important because of the impact that it brought to the shoreline, such as the destructive energy that breaking waves generates which would wipe anything that existed alongshore. Using the data collected from BMKG (Meteorology, Climatology, and Geophysics Council), maximum wind stress at the Panceng Sub-District was 17,2 m/s. Average effective fetch at Panceng Sub-District was 331,68 km with 5 m significant wave height and 11,2 s period. Breaking wave height at Panceng Sub-District is 5,5 m.